Polycystin-2 (TRPP2) regulation by Ca2+ is effected and diversified by actin-binding proteins - Cantero, Maria del Rocio (2015)
Calcium regulation of Ca2+-permeable ion channels is an important mechanism in the control of cell function. Polycystin-2 (PC2, TRPP2), a member of the transient receptor potential superfamily, is a nonselective cation channel with Ca2+ permeability. The molecular mechanisms associated with PC2 regulation by Ca2+ remain ill-defined. We recently demonstrated that PC2 from human syncytiotrophoblast (PC2hst) but not the in vitro translated protein (PC2iv), functionally responds to changes in intracellular (cis) Ca2+. In this study we determined the regulatory effect(s) of Ca2+-sensitive and -insensitive actin-binding proteins (ABPs) on PC2iv channel function in a lipid bilayer system. The actin-bundling protein α-actinin increased PC2iv channel function in the presence of cis Ca2+, although instead was inhibitory in its absence. Conversely, filamin that shares actin-binding domains with α-actinin had a strong inhibitory effect on PC2iv channel function in the presence, but no effect in the absence of cis Ca2+. Gelsolin stimulated PC2iv channel function in the presence, but not the absence of cis Ca2+. In contrast, profilin that shares actin-binding domains with gelsolin, significantly increased PC2iv channel function both in the presence and absence of Ca2+. The distinct effect(s) of the ABPs on PC2iv channel function demonstrate that Ca2+ regulation of PC2 is actually mediated by direct interaction(s) with structural elements of the actin cytoskeleton. These data indicate that specific ABP-PC2 complexes would confer distinct Ca2+-sensitive properties to the channel providing functional diversity to the cytoskeletal control of transient receptor potential channel regulation.